Money and monetary policy in less developed countries : a survey of issues and evidence - Coats, Warren L.; Khatkhate, Deena R. (Oxford ; New York : Pergamon Press, 1980)
Particularly in the last decade and a half, much thought has been given to the adaptation of monetary theory to monetary management in less developed countries, adding nuances to it, honing the techniques of analysis and building up a substantial body of empirical knowledge in the field. As a result, not only have the academics' perceptions of the underlying economic theory improved, but also the economic policy makers and central bankers in LDCs have been able to gain insights and understanding of the strengths and weaknesses of monetary policies. This volume of reading is designed to attenuate such difficulties by bringing together in one place selections of work in money, monetary policy, and the financial intermediation process of LDC's, that it is hoped will help, apart from becoming a useful teaching aid to universities, both students and policymakers alike.
"Readings in money and banking in the LDC's : bibliography": p. 763-810.
Includes bibliographies and index.
usc 17/10/18
Loans
Keywords: Monetary policy; Money; Finance; Developing countries